A conceptual study on the effect of Amaritadi ghanvati in urticaria : a review article. - Sason, Rajveer; Kumawat, Dinesh Kumar; Saini, Rashmi (International Research Journal of Ayurveda & Yoga, 2024)
Urticaria affects 20% of people at some point in their lifetime. In some cases, the disorder is relatively mild, recurrent and frustrating for both the patient and the physician. In other cases, it manifests as part of a spectrum of systemic anaphylaxis, which may be life threatening. The disability and distress caused by skin disorders can lead to serious impairment of quality of life, almost comparable to that experienced by patients with cardiovascular disease. To further complicate the issue, a fairly extensive list of diseases can cause Urticaria. Patients often see medical attention with the hope that a reversible cause can be identified. There are so many internal and external patent Ayurvedic drugs are available in market but still allergic skin diseases are not ended. Most of ingredients of Amaritadi ghanvati had raktshodhak property,dipan,pachan, krimighan, shothhar ,tridoshghan and immunomodulator properties,along with Vatasnabh which is vyavahi and vikasi in nature which proved in increasing the action of drugs. The drug had been taken from “Sahestrayog Pratham prakran 3/1.As we know that if we use poison in control and proper way, we get its medicinal effects as said in CharakSamhita.So present paper gives an idea about its work in urticaria.